Pedagogical model of curator activity for formation of student civil position at higher educational institution - Tatiana A. Miroshina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article shows that the education system should prepare people who can live in civil society and constitutional state and also create them. Literature theoretical analysis allowed us to determine the activities of the curator for the formation of student civic position as a focused and consciously carried out pedagogical process for the organization of socially significant activities of students and the development of self-government, necessary for self-realization of a person in society. In the course of the experimental work, a pedagogical model of the curator’s activity on the formation of the civic position of students was developed and implemented. It includes a number of components such as goals, objectives, content of the activities of curators and students at each stage of the formation of a civil position, methods, forms, means, criteria and indicators of the formation of a civil position. The implementation of this pedagogical model promotes the involvement of students in socially significant work, their active participation in various areas of interest, allows students to develop organizational skills, gain experience in participating in self- government and show a civil position. On the basis of developed the criteria and indicators we measured the level of formation of the civic position of students based on their introspection and expert assessments. The experts were individual group students, lecturers and curators. The study allowed us to conclude that the focused activities of the curators contribute to the activation of extracurricular activities of students, the development of student self-government of the group as a real form of student democracy with the corresponding rights, opportunities and responsibilities.